2022
DOI: 10.3390/pharmaceutics14112426
|View full text |Cite
|
Sign up to set email alerts
|

Enabling In Vivo Optical Imaging of an Osmium Photosensitizer by Micellar Formulation

Abstract: Osmium (Os)-based photosensitizers (PSs) exhibit unique broad, red-shifted absorption, favoring PDT activity at greater tissue depths. We recently reported on a potent Os(II) PS, rac-[Os(phen)2(IP-4T)](Cl)2 (ML18J03) with submicromolar hypoxia activity. ML18J03 exhibits a low luminescence quantum yield of 9.8 × 10−5 in PBS, which limits its capacity for in vivo luminescence imaging. We recently showed that formulating ML18J03 into 10.2 nm DSPE-mPEG2000 micelles (Mic-ML18J03) increases its luminescence quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As previously described, anthracene-9,10-dipropionic acid (ADPA) was used as a colorimetric probe at 378 nm to detect singlet oxygen generation. 10 , 20 , 21 While the fluorescence changes in ADPA for singlet oxygen detection are more sensitive than the absorbance changes, absorbance was monitored as to avoid fluorescence artifacts arising from other factors such as contaminants or quenching. 37 It was found that ADPA decreased in absorbance at 378 nm for all samples ( Figure 4 A).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described, anthracene-9,10-dipropionic acid (ADPA) was used as a colorimetric probe at 378 nm to detect singlet oxygen generation. 10 , 20 , 21 While the fluorescence changes in ADPA for singlet oxygen detection are more sensitive than the absorbance changes, absorbance was monitored as to avoid fluorescence artifacts arising from other factors such as contaminants or quenching. 37 It was found that ADPA decreased in absorbance at 378 nm for all samples ( Figure 4 A).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For SOSG and HPF samples, fluorescence was measured with 460 nm excitation and 530 nm emission (bottom read, 100 gain, 20 μs integration time). ADPA was used as a colorimetric probe for singlet oxygen generation as previously described. ,, The absorbance of ADPA samples was measured at 378 nm (25 flashes, 0 ms settle time).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI values for lipid formulations of ML18J03 are (with broadband visible light) as high as 1.3 × 10 4 and 4.4 × 10 4 for liposomal and micellar formulations, respectively. Micellar formulation of ML18J03 has also been used recently to enable in vivo imaging of head and neck tumors due to enhanced tumor selectivity and luminescence (4).…”
Section: Commentarymentioning
confidence: 99%
“…This formulation not only improved the luminescence of the photosensitizer but also increased its tumor selectivity. By encapsulating the photosensitizer within micelles, researchers were able to enhance its accumulation in tumor tissues and achieve a higher level of selectivity, addressing the challenge posed by the photosensitizer’s low-luminescence quantum yield [ 1 ].…”
mentioning
confidence: 99%